Techniczne metody ochrony przeciwpowodziowej w Polsce = The technical methods flood protection - Kołodziejczyk, Urszula; Żebrowska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main purpose of this thesis was taking look back on the current problems related to effective flood protection and methods applied in grapple with the elements as high water. In this article the particular pressure was taken on two sorts of buffer i.e. active and passive prevention which are executing with cooperation of the flood's protection methods.
Keywords: powódź; czynna i bierna ochrona przeciwpowodziowa; technicznemetody ochrony przeciwpowodziowej; flood; active and passive flood protection; technical methodsof flood protection